2018
DOI: 10.1021/acs.est.8b02637
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation and Biotransformation of Triclosan and Galaxolide in the Freshwater Oligochaete Limnodrilus hoffmeisteri in a Water/Sediment Microcosm

Abstract: Personal care products are widely used in our daily life in considerable quantities and discharged via the down-the-drain route to aquatic environments, resulting in potential risks to aquatic organisms. We investigated bioaccumulation and biotransformation of two widely used personal care products, triclosan (TCS) and galaxolide (HHCB) spiked to sediment, in the oligochaete worm Limnodrilus hoffmeisteri in water/sediment microcosms. After 7 days of sediment exposure to 3.1 μg of TCS or HHCB/g of dry weight se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Galaxolide has been detected at all sampling sites in this study and also in marine sediments and biota from Singapore, 59 in suspended particulate matter samples from River Elbe, 60 and in sediments from the rivers Havel and Spree (Germany), which are tributaries of River Elbe, 61 and its bioaccumulation potential has previously been shown. 62,63 Unfortunately, the reported values were in dry weight/wet weight units, hence making it difficult to compare with our study. However, the wide distribution of Galaxolide supports the study by von der Ohe et al 64 who found that the measured concentrations of Galaxolide in the environment frequently exceeded the predicted no effect concentrations (PNECs).…”
Section: Resultsmentioning
confidence: 73%
“…Galaxolide has been detected at all sampling sites in this study and also in marine sediments and biota from Singapore, 59 in suspended particulate matter samples from River Elbe, 60 and in sediments from the rivers Havel and Spree (Germany), which are tributaries of River Elbe, 61 and its bioaccumulation potential has previously been shown. 62,63 Unfortunately, the reported values were in dry weight/wet weight units, hence making it difficult to compare with our study. However, the wide distribution of Galaxolide supports the study by von der Ohe et al 64 who found that the measured concentrations of Galaxolide in the environment frequently exceeded the predicted no effect concentrations (PNECs).…”
Section: Resultsmentioning
confidence: 73%
“…The model has successfully predicted the time-course internal concentrations of the antibiotics, indicating that the principle of passive diffusion is suitable to characterize bioaccumulation of chemicals in sea cucumbers. However, sea cucumbers are benthic deposit-feeders that can be exposed to sediment-associated pollutants under field conditions because of their ingestion activities and direct contact with sediments. , Therefore, future work is needed to explore accumulation of sediment-associated chemicals in sea cucumbers and to incorporate sediment exposure into the toxicokinetic model so as to increase the prediction accuracy of models. Further studies may also develop and validate MCT models for BTPs through measuring their time-course internal concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…15−17 The occurrence and fate of pollutants change under the influence of environmental media and organisms because of their interaction. 16,18 Meanwhile, the interference of pollutants can disturb the balance of the ecosystem and harm living organisms. 19 Zebrafish is an important organism for monitoring water quality safety due to its high sensitivity to pollutants.…”
Section: ■ Introductionmentioning
confidence: 99%